Quantum wave packet study of S(1D)+D2?SD+D reaction - Bulut, N; Gogtas, F; Akpinar, S (Elsevier, 2005)
S(D-1) + D-2 --> SD + D reaction has been studied by using a time-dependent quantum real wave packet method. State-to-state and state-to-all reactive scattering probabilities for a broad range of energy are calculated at zero total angular momentum. The state-to-state probabilities show many sharp peaks that ascribed to reactive scattering resonances. The probabilities for J > 0 are estimated from accurately computed J = 0 probabilities by using J-shifting approximation. The integral cross-sections are calculated for a large energy range. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Reaction Dynamics; Scattering; S(D-1)+H-2; State; Model; Hd